EVALUATING THE PERFORMANCE OF GPS-BASED NAVIGATION SYSTEMS DURING GEOMAGNETIC STORMS USING DIFFERENT PSEUDORANGE MEASUREMENTS - Adewale, A. O.; Oyeyemi, E. O.; Oyebola, O. O.; Odeyemi, O. O.; Olugbon, B.; Odetola, J. A.; Akindolire, R. T.; Obafaye, A. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Geomagnetic storms have significant space-weather effects on space and ground-based Global Positioning System (GPS). The signals from GPS suffer degradation and delay during propagation from space to ground-based receivers, as they travel through the ionosphere. Comparison of GPS positioning 3-D vertical (MRSE) and horizontal (DRMS) root mean squared positioning errors obtained from different pseudorange measurements at low, mid and high latitude stations has been reported. GPS observation data were examined from 6th-12th November 2004, using different pseudorange measurements. Our results show that geomagnetic storms and latitudinal variation have little significance on the positioning. Dual frequency receivers recorded low errors compared to single frequency receivers. Generally, single-frequency GPS receivers on L1 C/A and L1 P codes measurement are more accurate and reliable than the one on L2 P-code. Measurement on the ionosphere-free combination dual frequency receivers (C/A on L1 and P on L2) recorded more significant errors compared to the ionosphere-free L1/L2 combination (P on L1 and P on L2). Our results show that other factors played a significant role in poor positioning errors.